How to build your very own little free library : 11 mini structures you can build - Schmidt, Philip (Cool Springs Press, an imprint of the Quarto Group, 2025)
"How to Build Your Very Own Little Free Library is your source of inspiration and how-to knowledge. Illustrated with step-by-step photos, this newly updated book covers planning and design--with 11 complete plans and materials lists--plus building, decorating, installation, and maintenance for a variety of book-sharing boxes"--